The Risks Faced by Adolescent Workers in the United Kingdom. (February 2016) - Hobbs, Sandy; McKechnie, Jim; Simpson, Amanda
Most young people in the United Kingdom undertake some kind of part-time employment before they reach the minimum school-leaving age. The United Kingdom claims to protect this group of workers and meet its obligations under Article 32 of the United Nations Convention on the Rights of the Child by legislation. Research clearly shows that the system is ineffective and fails to adequately protect young workers. Empirical investigations indicate that there is reason for concern about this situation. This article considers the risks to young workers with respect to education, health and safety and financial exploitation. Faced with such evidence successive governments have shown themselves unwilling to take effective action in this area. We consider potential explanations for such inaction.